Frequency of Serum Ferritin Level in Non-Anemic Pregnant Women Presenting at Hospital - Nahil Shams, Amna Aslam, Hina Amanullah, Kiran Memon, Samraz, Afnan Rizwan, Kiran Aamir, Aamir Ramzan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine mean serum ferritin level in non-anemic pregnant women presenting at Isra University Hospital during their antenatal visit. Study Design: Cross sectional study. Place and Duration: Department of Obstetrics and Gynecology at Isra University Hospital Hyderabad. January 2019-Jun 2019 Methods: A total of 78 non-anemic pregnant women with hemoglobin level>11gm/dl during 1st and 3rd trimester and>10.5gm/dl during 2nd trimester (as defined by CDC Criteria for anemia) were included in this study. A detailed history was obtained. All variable information was recorded in predesigned Performa. Results: The average age of women was 30.15±3.36 years. Mean serum ferritin level in non-anemic pregnant women was 13.05±5.088 nm/dl. Out of 78 cases 43(55.1%) of non-anemic female were found to have Iron deficiency state on the basis of serum ferritin estimates ≤12 ng/ml. Conclusion: In pregnancy, plasma volume, erythropoesis, and fetoplacental unit demand rise, causing iron defficiency. All pregnant women should be tested for iron status. Proper ID surveillance among pregnant women ensures accurate recording, assessment, and introduction of serum ferritin test early in the first trimester with the first ANC visit to catch afflicted pregnant. Keywords: serum ferritin, Non-anemic pregnant women, Iron deficiency anemia